2009
DOI: 10.1002/smj.766
|View full text |Cite
|
Sign up to set email alerts
|

Too much love in the neighborhood can hurt: how an excess of intensity and trust in relationships may produce negative effects on firms

Abstract: This study aims to provide a better understanding of the effect of social networks on innovation through the analysis of territorial agglomerations of firms. Critical voices argue that the same mechanisms that form the basis of efficient, continuous improvements of clustered firms can also be considered as limitations. We suggest that the impact of social capital decreases beyond a certain point of development. In fact, the effect of social interactions and trust on firm value creation can be described as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
171
1
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 250 publications
(199 citation statements)
references
References 71 publications
(69 reference statements)
11
171
1
10
Order By: Relevance
“…It is in the growth period when firms can benefit most from the local network. Previous studies have also observed the nonlinear effect of local networks on innovation and other performance measures, similar to the one observed in this research (Mcfadyen and Cannella, 2004;Molina-Morales and Martínez-Fernández, 2009). …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It is in the growth period when firms can benefit most from the local network. Previous studies have also observed the nonlinear effect of local networks on innovation and other performance measures, similar to the one observed in this research (Mcfadyen and Cannella, 2004;Molina-Morales and Martínez-Fernández, 2009). …”
Section: Discussionsupporting
confidence: 90%
“…Following Gulati (1995), firms repeating interactions with other co-located firms tend to develop trust and this induces firms to behave loyally, therefore reducing the mutual fear that others will act opportunistically. Firms tend to reinforce their local relationships with frequent visits to and meetings with other firms, or informal encounters, and with personal proximity, which increases the willingness of firms to share knowledge (Molina-Morales and Martínez-Fernández, 2009). In this environment, the opportunism risk is reduced, firms tend to find more opportunities and time for knowledge transfer and there is a feeling of reliability and positive expectations about future relations (Levin and Cross, 2004;Phelps et al, 2012).…”
Section: Theoretical Framework: a Firm's Knowledge Transfer Over Timementioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the increasing relevance of the internal diversity between firms in the cluster (Giuliani, 2005;Boshma and Ter Wal, 2007), and secondly, the indirect, non-linear effects of dense internal ties which can alter key features of the cluster's characteristics (Giuliani and Bell, 2005;Waxell and Malmberg, 2007;Molina-Morales and Martínez-Fernández, 2009). …”
Section: Introductionmentioning
confidence: 99%